Ceramic tile with golden velvet texture and preparation method thereof

A ceramic tile composition with specific glaze layers addresses the challenge of achieving three-dimensional marble-like textures and improved durability by using tailored chemical formulations and particle sizes, resulting in a delicate and durable velvet texture.

CN119219428AActive Publication Date: 2024-12-31GUANGDONG NEWPEARL CERAMIC GRP CO LTD +1

Patent Information

Application Number
CN202411751802.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2024-12-31
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Ceramic tiles with velvet or velvet-like textures struggle to achieve three-dimensional fine concave and convex textures similar to natural marble effects while maintaining a delicate and warm texture, often compromising wear resistance and anti-fouling performance due to the use of soft materials in the glaze.

Method used

A ceramic tile composition comprising a base glaze layer, digital protection glaze layer, and surface glaze layer, each with specific chemical formulations and particle sizes, to create a dense and warm texture with improved hardness and wear resistance, using components like corundum, high-petroleum silicon frit, and barium strontium ice stone crystals.

Benefits of technology

The ceramic tiles achieve both fine concave and convex texture effects with soft and delicate surfaces, exhibiting good hardness, wear resistance, and anti-fouling performance, enhancing the product's overall quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219428A_ABST
    Figure CN119219428A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramics, and particularly discloses a ceramic tile with a golden velvet texture and a preparation method of the ceramic tile. The ceramic tile sequentially comprises a bottom blank layer, a ground glaze layer, a pattern layer, a functional ink layer, a digital protective glaze layer and a surface glaze layer from bottom to top, the digital protective glaze is obtained by sequentially applying the ground glaze, the digital protective glaze and the surface glaze which are specially adjusted and firing. The formula of the ground glaze, the digital protective glaze and the surface glaze is coordinated and improved, so that the ceramic tile has a fine concave-convex fluctuating texture effect and a smooth and fine texture effect, and also has the characteristics of better hardness, wear resistance, antifouling property and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramics, and in particular relates to a ceramic tile with a gold velvet texture and a preparation method thereof. Background Art

[0002] With the development of matte ceramic tiles and consumers' love for matte ceramic tiles, matte ceramics not only pursue beautiful textures and colors, but also innovate in the texture of the ceramic surface, and have been moving towards delicate texture, warm and soft touch. Currently, velvet, skin glaze, smooth surface and other glazed ceramic tiles have appeared on the market, and their sales are getting better and better. The pursuit of warm texture and delicate touch has also changed the cold and hard feeling that ceramic tiles give people, and has a good market prospect.

[0003] At present, the production technology of glazed tiles mainly adjusts the glaze formula to reduce the high-temperature viscosity of the glaze. After firing, the glaze surface is relatively flat, and the glaze surface contains more glass phase, thus forming a delicate and warm effect to achieve velvety and skin-textured glazed ceramic tiles. However, consumers also like imitation marble ceramic products very much. The fine concave and convex texture on the surface of natural marble has a very natural effect, which is formed by the deposition of various elements and geological movements. Ceramic tiles simulate its beautiful effect, and can form an effect with fine concave and convex gaps through inkjet digital ink, but the natural marble effect with fine texture requires a glaze with a slightly higher high-temperature viscosity and a slightly higher formula temperature. In this way, when the product glaze has a more three-dimensional texture, the glaze texture is relatively hard, and it is difficult to form a warm skin texture effect. By adjusting the glaze formula, the glaze surface can have a warm, delicate and smooth texture, but it is often necessary to add softer materials, which are prone to collapse after firing and it is difficult to ensure fine uneven texture. Due to the use of soft materials in the glaze, the glaze surface has poor wear resistance and hardness, and poor anti-fouling performance after application, which makes the tiles easy to get dirty, limiting the application range of the product.

[0004] Therefore, how to solve the problem that ceramic tiles with skin, velvet and velvet texture are difficult to form three-dimensional fine concave and convex textures similar to natural marble effects, and at the same time the delicate and warm texture of the glaze causes the product to have low wear resistance and poor anti-fouling performance is of great significance to how to improve product quality. Summary of the invention The purpose of the present invention is to solve the deficiencies of the prior art. Based on this, the first aspect of the present invention provides a ceramic tile with a gold velvet texture, which includes, from bottom to top, a base layer, a base glaze layer, a pattern layer, a functional ink layer, a digital protection glaze layer, and a surface glaze layer; The base glaze layer is formed by base glaze, and the base glaze comprises, by weight: 4-8 parts of air knife clay, 16-20 parts of calcined kaolin, 3-6 parts of calcined alumina, 10-15 parts of barium-containing frit, 15-23 parts of potassium feldspar, 12-20 parts of sodium feldspar, 12-18 parts of zircon white frit, 3-6 parts of burned talc, and 3-6 parts of wollastonite; The digital protection glaze layer is formed by a digital protection glaze, which includes, by weight: 40-50 parts of an organic solvent and 50-60 parts of an inorganic glaze component; the organic solvent includes, by weight percentage: 45%-60% isooctyl laurate, 35%-50% ethyl acetate, 3%-6% dispersant, 0.1%-0.2% suspending agent, 0.2%-0.3% defoaming agent, 0.3%-0.6% leveling agent, and 0.15%-0.3% pH adjuster; the inorganic glaze component includes, by weight percentage: 17.35%-20.17% Al2O3, 55.68%-60.37% SiO2, 1.38%-2.65% K2O, 1.95%-3.01% Na2O, 2.13%-3.68% Bi2O3, 2.36%-4.65% B2O3, and 0.15%-0.3% pH adjuster. 4.37%-6.58%, SrO 3.65%-5.68%; The surface glaze layer is formed by a surface glaze, and the surface glaze comprises, by weight: 4-8 parts of ball clay, 4-7 parts of corundum, 9-18 parts of high borosilicate frit, 18-25 parts of boron bismuth frit, 30-45 parts of monovalent oxide frit, 6-10 parts of barium carbonate, and 6-10 parts of strontium carbonate; The average particle size of the particles in the above-mentioned base glaze is 2 μm-8 μm; the average particle size of the particles in the above-mentioned digital protection glaze is 50 nm-100 nm; and the average particle size of the particles in the above-mentioned surface glaze is 1 μm-8 μm.

[0005] The present invention achieves the effect of ceramic tiles having both fine concave and convex texture effects and soft and delicate texture by overall research and design of base glaze, digital protective glaze and surface glaze, while also having the characteristics of good hardness, wear resistance and anti-fouling performance.

[0006] Among them, the surface glaze is the glaze layer that directly contacts the outside world. Based on the goals of better physical properties, softer, warmer and more delicate texture and fine surface texture, and the current glaze formula that can achieve the above-mentioned multiple effects, the surface glaze designed by the present invention adopts ball clay mainly to ensure the suspension of glaze slurry and prevent the glaze slurry from settling, while providing the main skeleton components Al2O3 and SiO2; the corundum used is calcined Al2O3, which has the characteristics of high hardness and high chemical stability, and is more conducive to improving the transparency of the glaze than Al2O3 (for surface glaze, transparency is extremely important to ensure the clear display of the pattern); the high-petroleum silicon frit used (a frit made of SiO2 and boron trioxide as the main raw materials, the main components by mass percentage include: Al2O3 13.25%-15.35%, SiO2 68.39%-71.25%, B2O3 8.67%-11.25%, K2O 2.35%-4.67%, Na2O 1.54%-2.68%, the rest are trace impurities and reduced as appropriate) and the boron bismuth frit (the main components by mass percentage include: SiO2 56.31%-60.37%, Al2O313.64%-15.77%, B2O3 11.32%-14.65%, Bi2O3 8.62%-9.67, K2O 1.35%-2.91%, Na2O 1.11%-2.08%, the rest are trace impurities and reduced as appropriate) mainly uses boron oxide tetrahedron to replace part of silicon oxide tetrahedron, thereby increasing the hardness of the glaze layer. At the same time, due to the presence of bismuth oxide, it can be filled in the glass phase to replace part of Al2O3, making the glaze layer more moist and delicate. At the same time, after firing, it can ensure the high-temperature viscosity of the glaze so that the glaze layer maintains a fine texture after firing; the monovalent oxide frit used (the main components by mass percentage include: K2O 4.56%-6.67%, Na2O 6.21%-9.34%, Li2O4.63%-6.46%, SiO2 59.31%-63.34%, Al2O3 16.69%-18.35%, the rest are trace impurities and reduced as appropriate), mainly by utilizing the low-temperature fluxing effect of its monovalent oxide to promote the full reaction of the glaze layer, form a glass phase, and increase the warmth of the glaze layer; and the barium carbonate and strontium carbonate used can form barium strontium ice stone crystals after firing, which have the characteristics of a layered structure and can make the glaze surface have a smooth texture.The overall chemical composition of the surface glaze includes, by mass percentage, Al2O315.38%-17.65%, SiO2 52.21%-54.61%, K2O 2.31%-3.45%, Na2O 1.35%-2.45%, Li2O 1.02%-1.89%, B2O3 6.65%-8.58%, Bi2O3 3.65%-5.94%, BaO 4.31%-5.98%, SrO 4.64%-5.75%, and the rest are trace impurities and discretionary reductions.

[0007] Secondly, the present invention has also conducted special research and design on the composition of the bottom glaze based on the special design of the above-mentioned surface glaze. In the bottom glaze formula of the present invention, the air knife clay used mainly provides aluminum oxide and SiO2 as the main skeleton, and at the same time has good suspension, ensuring the characteristic of non-precipitation of the glaze; the calcined kaolin used is to provide aluminum oxide and SiO2 as the main skeleton. At the same time, when the calcined kaolin is applied to the glaze, it shrinks less after firing, and the glaze layer is more compact and delicate; the barium-containing frit used is a frit fired with an oxide containing BaO, which mainly provides BaO, and can interact with the above-mentioned digital protection glaze and the above-mentioned surface glaze during firing to form barium strontium ice stone crystals, which have a layered structure It not only exists in the surface glaze layer, but also in the bottom glaze layer, which solves the problem of the hard bottom of conventional glazes; the main function of the potassium feldspar and sodium feldspar used is to provide monovalent oxides, accelerate the firing speed and thus facilitate the formation of crystals; the main function of the zirconium white frit used is to increase the whiteness of the glaze layer and cover the color of the bottom layer, and the introduction of ZrO2 in the form of zirconium white frit compared to the more common zirconium silicate introduction method not only has better covering ability, but also has better solubility than zirconium silicate, which can avoid the problem of rough glaze surface caused by zirconium silicate; the burned talc used is mainly to provide alkaline earth metal oxide MgO, which has a good high-temperature fluxing effect, and has the effect of making the glaze surface smoother after firing.

[0008] In addition, the present invention further provides the above-mentioned digital protection glaze layer containing the above-mentioned digital protection glaze designed with a specific formula between the above-mentioned base glaze layer and the above-mentioned surface glaze layer. The average particle size (50 nm-100nm) of the particles in the above-mentioned digital protection glaze is smaller than the above-mentioned base glaze (average particle size of 2 μm-8 μm) and the above-mentioned surface glaze (average particle size of 1 μm-8 μm), so that the particles in the above-mentioned digital protection glaze can be effectively filled in the gaps between the other two, making the glaze layer denser, and various crystal phases are evenly distributed after firing, making the overall glaze layer more delicate and warm. In the above-mentioned digital protection glaze, the monovalent oxide is mainly used as a flux, and the alkaline earth metal oxide and the neutral oxide Bi2O3, B2O3 can make the above-mentioned digital protection glaze more completely combined with the base glaze and the surface glaze, and have a more suitable acidity coefficient.

[0009] Among them, the above-mentioned organic solvents include, by mass percentage: 45%-60% isooctyl laurate, 35%-50% ethyl acetate, 3%-6% dispersant, 0.1%-0.2% suspending agent, 0.2%-0.3% defoaming agent, 0.3%-0.6% leveling agent, and 0.15%-0.3% pH adjuster.

[0010] The chemical components of the above-mentioned base glaze include, by mass percentage, Al2O3 21.04%-24.56%, SiO2 50.24%-53.29%, K2O 1.34%-2.57%, Na2O 1.87%-2.65%, CaO 0.80%-1.61%, MgO 1.21%-2.04%, BaO 6.31%-8.24%, and ZrO2 6.30%-8.64%. The above-mentioned base glaze layer is formed by preparing the above-mentioned base glaze into a first slurry, and the preparation method of the above-mentioned first slurry includes the following process: mixing the above-mentioned base glaze with 38-40 parts of water, 0.13-0.18 parts of sodium carboxymethyl cellulose, and 0.25-0.35 parts of sodium tripolyphosphate, and ball milling to obtain the above-mentioned first slurry.

[0011] The surface glaze layer is formed by making the surface glaze into a second slurry. The preparation method of the second slurry includes the following steps: mixing the surface glaze with 38-40 parts of water, 0.15-0.2 parts of sodium carboxymethyl cellulose and 0.3-0.4 parts of sodium tripolyphosphate, and ball milling to obtain the second slurry.

[0012] The second aspect of the present invention provides a method for preparing the above-mentioned ceramic tile with a velvet texture, comprising the following steps: applying the above-mentioned base glaze on the above-mentioned base layer, then printing patterns and functional inks in sequence, then applying the above-mentioned digital protective glaze and applying the above-mentioned surface glaze; and firing to obtain the above-mentioned ceramic tile.

[0013] The moisture content of the base layer is less than 0.3%, and the strength is 1.8 MPa-2.4 MPa; the application amount of the base glaze is 380 g / m 2 -450 g / m 2 ; The application amount of the above digital protective glaze is 70 g / m 2 -100 g / m 2 ; The application amount of the above surface glaze is 180 g / m 2 -240 g / m 2 The above-mentioned firing conditions include: firing time of 50 min-60 min, firing temperature of 1180 ℃-1190 ℃.

[0014] It should be noted that all “%” in the present invention refers to “mass percentage”, which is equivalent to “mass percentage content” and “mass fraction”; it should also be noted that “applied glaze” referred to in the art is equivalent to “slurry made by applying glaze”, which is common knowledge for technicians in the art and will not cause any ambiguity or misunderstanding, and will not affect the understanding and implementation of the technical solution.

[0015] The beneficial effects of the present invention are as follows: the present invention achieves the effect of ceramic tiles having both fine convex and concave texture effects and soft and delicate texture by coordinating and improving the base glaze, digital protective glaze and surface glaze formula, and also has the characteristics of good hardness, wear resistance and anti-fouling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Shown is a picture of a ceramic tile with a gold velvet texture obtained in Example 1; Figure 2 Shown is a picture of the ceramic tile prepared in Comparative Example 1; Figure 3 Shown is a schematic diagram of the structure of a ceramic tile with a gold velvet texture prepared in Example 1. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments and drawings to clearly and completely describe the concept, specific structure and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0018] Example 1 A ceramic tile with a golden velvet texture, the structural diagram of which is as follows Figure 3 As shown, from bottom to top, it includes a base layer, a base glaze layer, a pattern layer, a functional ink layer, a digital protection glaze layer, and a surface glaze layer.

[0019] The base glaze layer is formed by the first slurry made of the base glaze, and the base glaze includes, by weight: 6 parts of air knife clay, 18 parts of calcined kaolin, 4.5 parts of calcined alumina, 12.5 parts of barium frit, 19 parts of potassium feldspar, 16 parts of sodium feldspar, 15 parts of zircon white frit, 4.5 parts of calcined talc, and 4.5 parts of wollastonite. Its chemical components include, by mass percentage: Al2O3 22.80%, SiO2 51.76%, K2O 1.95%, Na2O 2.26%, CaO 1.20%, MgO 1.62%, BaO 7.27%, and ZrO2 7.47%. The preparation process of the first slurry includes: mixing the above-mentioned base glaze with 38 parts of water, 0.15 parts of sodium carboxymethyl cellulose, and 0.3 parts of sodium tripolyphosphate, and ball milling to obtain the first slurry; the average particle size of the particles in the first slurry (that is, the average particle size of the particles of the base glaze) is 4 μm-6 μm.

[0020] The digital protection glaze layer is formed by the digital protection glaze, which includes 45 parts of organic solvent and 55 parts of inorganic glaze components by weight; the organic solvent includes 52% of isooctyl laurate, 43% of ethyl acetate, 4% of dispersant (sodium polyacrylate), 0.15% of suspending agent (hexamethyldisilazane), 0.25% of defoamer (ethylene glycol), 0.4% of leveling agent (Taiyang TY01), and 0.2% of pH adjuster (triethanolamine) by mass percentage; the inorganic glaze components include 18.76% of Al2O3, 58.02% of SiO2, 2.01% of K2O, 2.48% of Na2O, 2.9% of Bi2O3, 3.50% of B2O3, 5.47% of BaO, and 4.66% of SrO by mass percentage. The average particle size of the particles of the digital protection glaze (that is, the average particle size of the particles of the inorganic glaze components) is 70 nm.

[0021] The surface glaze layer is formed by a second slurry made of the surface glaze, and the surface glaze includes, by weight: 6 parts of ball clay, 5.5 parts of corundum, 13.5 parts of high borosilicate frit, 21.5 parts of boron bismuth frit, 37.5 parts of monovalent oxide frit, 8 parts of barium carbonate, and 8 parts of strontium carbonate. Its chemical components, by mass percentage, include: Al2O3 16.51%, SiO2 53.41%, K2O 2.88%, Na2O 1.90%, Li2O 1.45%, B2O3 7.61%, Bi2O34.79%, BaO 5.14%, and SrO 5.19%. The preparation process of the second slurry includes: mixing the above-mentioned surface glaze with 39 parts of water, 0.15 parts of sodium carboxymethyl cellulose, and 0.4 parts of sodium tripolyphosphate, and ball milling to obtain the second slurry; the average particle size of the particles in the second slurry (that is, the average particle size of the particles of the surface glaze) is 3 μm-5 μm.

[0022] The preparation method of the ceramic tile with golden velvet texture comprises the following steps: The bricks were pressed to form a base layer, which was then dried to a moisture content of 0.3% and a strength of 2.1 MPa. A base glaze was applied on the base layer with a glaze amount of 420 g / m 2 ; Enter the inkjet printing device to print fine marble patterns and functional inks, and then enter the second inkjet machine to print digital protective glaze. The printing volume of digital protective glaze is 80 g / m 2 Then it enters the surface glaze spraying equipment to spray the surface glaze, the spraying amount is 200 g / m 2 ; Finally, it enters the firing kiln for firing, the firing time is 58 minutes, and the firing temperature is 1180 ℃; after the firing is completed, the edge is ground to obtain the ceramic tile with a golden velvet texture. Figure 1 As shown, it can be seen that it has the effect of velvet texture and uneven texture, and has the effect of restoring marble.

[0023] Example 2 A ceramic tile with a velvet texture, which is different from Example 1 in that: the base glaze contains 10 parts of barium frit; the chemical components of the base glaze include, by mass percentage, Al2O3 23.50%, SiO2 51.96%, K2O 1.94%, Na2O2.28%, CaO 1.22%, MgO 1.63%, BaO 6.31%, and ZrO2 7.51%. Others are the same as Example 1.

[0024] Example 3 A ceramic tile with a velvet texture, which is different from Example 1 in that: the base glaze contains 15 parts of barium frit; the chemical components of the base glaze include, by mass percentage, Al2O3 22.60%, SiO2 50.81%, K2O 1.93%, Na2O2.17%, CaO 1.18%, MgO 1.58%, BaO 8.21%, and ZrO2 7.39%. Others are the same as Example 1.

[0025] Example 4 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the average particle size of the bottom glaze particles is 2 μm. The rest is the same as Example 1.

[0026] Example 5 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the average particle size of the bottom glaze particles is 8 μm. The rest is the same as Example 1.

[0027] Example 6 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the Bi2O3 in the digital protective glaze is 2.13%. Other aspects are the same as Example 1.

[0028] Example 7 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the Bi2O3 in the digital protective glaze is 3.68%. Other aspects are the same as Example 1.

[0029] Example 8 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the B2O3 in the digital protective glaze is 2.36%. Other aspects are the same as Example 1.

[0030] Example 9 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the B2O3 in the digital protective glaze is 4.65%. Other aspects are the same as Example 1.

[0031] Example 10 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the average particle size of the digital protective glaze particles is 50 nm. Other aspects are the same as Example 1.

[0032] Embodiment 11 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the average particle size of the digital protective glaze particles is 100 nm. Other aspects are the same as Example 1.

[0033] Example 12 A ceramic tile with a velvet texture, which is different from Example 1 in that: the surface glaze contains 9 parts of high borosilicate frit; the chemical components of the surface glaze include, by mass percentage, Al2O3 17.51%, SiO2 52.21%, K2O2.81%, Na2O 1.88%, Li2O 1.39%, B2O3 6.68%, Bi2O3 5.69%, BaO 5.12%, and SrO 5.29%. Others are the same as Example 1.

[0034] Embodiment 13 A ceramic tile with a velvet texture, which is different from Example 1 in that: the surface glaze contains 18 parts of high borosilicate frit; the chemical components of the surface glaze include, by mass percentage, Al2O3 15.98%, SiO2 54.61%, K2O2.98%, Na2O 1.80%, Li2O 1.40%, B2O3 8.58%, Bi2O3 3.68%, BaO 5.02%, and SrO 4.94%. Others are the same as Example 1.

[0035] Embodiment 14 A ceramic tile with a velvet texture, which is different from Example 1 in that: the boron-bismuth frit in the surface glaze is 18 parts; the chemical components of the surface glaze include, by mass percentage, Al2O3 17.05%, SiO2 53.61%, K2O 2.94%, Na2O 2.01%, Li2O 1.35%, B2O3 6.68%, Bi2O3 3.67%, BaO 4.88%, and SrO 5.05%. Others are the same as Example 1.

[0036] Embodiment 15 A ceramic tile with a velvet texture, which is different from Example 1 in that: the boron-bismuth frit in the surface glaze is 25 parts; the chemical components of the surface glaze include, by mass percentage, Al2O3 16.28%, SiO2 53.25%, K2O 2.71%, Na2O 1.85%, Li2O 1.42%, B2O3 8.48%, Bi2O3 5.88%, BaO 4.67%, and SrO 4.90%. Others are the same as Example 1.

[0037] Example 16 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the average particle size of the surface glaze particles is 1 μm. The rest is the same as Example 1.

[0038] Embodiment 17 A ceramic tile with a golden velvet texture, which is different from Example 1 in that the average particle size of the surface glaze particles is 8 μm. The rest is the same as Example 1.

[0039] Comparative Example 1 A ceramic tile, which is different from Example 1 in that: the base glaze contains 8 parts of barium frit; the chemical components of the base glaze include, by mass percentage, Al2O3 23.70%, SiO2 52.36%, K2O 2.15%, Na2O 3.06%, CaO 1.21%, MgO1.42%, BaO 6.21%, and ZrO2 6.77%. Other components are the same as Example 1.

[0040] Comparative Example 2 A ceramic tile, which is different from Example 1 in that: the base glaze contains 17 parts of barium frit; the chemical components of the base glaze include, by mass percentage, Al2O3 21.70%, SiO2 51.86%, K2O 1.90%, Na2O 2.28%, CaO 1.29%, MgO1.64%, BaO 10.20%, and ZrO2 7.38%. Other components are the same as Example 1.

[0041] Comparative Example 3 A ceramic tile, which is different from Example 1 in that the average particle size of the bottom glaze particles is 0.8 μm. Other aspects are the same as Example 1.

[0042] Comparative Example 4 A ceramic tile, which is different from Example 1 in that the average particle size of the bottom glaze particles is 20 μm. Other aspects are the same as Example 1.

[0043] Comparative Example 5 A ceramic tile, which is different from the embodiment 1 in that the Bi2O3 in the digital protective glaze is 1.89%. The rest is the same as the embodiment 1.

[0044] Comparative Example 6 A ceramic tile, which is different from the embodiment 1 in that the Bi2O3 in the digital protective glaze is 4.01%. The rest is the same as the embodiment 1.

[0045] Comparative Example 7 A ceramic tile, which is different from the embodiment 1 in that the B2O3 in the digital protective glaze is 2.05%. The rest is the same as the embodiment 1.

[0046] Comparative Example 8 A ceramic tile, which is different from Example 1 in that the B2O3 content in the digital protective glaze is 4.87%. Other aspects are the same as Example 1.

[0047] Comparative Example 9 A ceramic tile, which is different from Example 1 in that the average particle size of the digital protective glaze particles is 150 nm. Other aspects are the same as Example 1.

[0048] Comparative Example 10 A ceramic tile, which is different from Example 1 in that: the surface glaze contains 7 parts of high borosilicate frit; the chemical components of the surface glaze include, by mass percentage, Al2O3 18.55%, SiO2 50.11%, K2O 3.55%, Na2O 2.56%, Li2O1.95%, B2O3 4.15%, Bi2O3 4.65%, BaO 5.11%, and SrO 4.95%. Other components are the same as Example 1.

[0049] Comparative Example 11 A ceramic tile, which is different from Example 1 in that: the surface glaze contains 20 parts of high borosilicate frit; the chemical components of the surface glaze include, by mass percentage, Al2O3 15.38%, SiO2 55.66%, K2O 2.35%, Na2O 1.36%, Li2O1.36%, B2O3 9.28%, Bi2O3 3.99%, BaO 4.69%, and SrO 4.89%. Other components are the same as Example 1.

[0050] Comparative Example 12 A ceramic tile, which is different from Example 1 in that: the boron-bismuth frit in the surface glaze is 16 parts; the chemical components of the surface glaze include, by mass percentage, Al2O3 18.75%, SiO2 55.61%, K2O 2.47%, Na2O 1.74%, Li2O1.47%, B2O3 4.55%, Bi2O3 2.55%, BaO 4.96%, and SrO 5.05%. Other components are the same as Example 1.

[0051] Comparative Example 13 A ceramic tile, which is different from Example 1 in that: the boron-bismuth frit in the surface glaze is 27 parts; the chemical components of the surface glaze include, by mass percentage, Al2O3 15.31%, SiO2 51.35%, K2O 2.70%, Na2O 1.64%, Li2O1.34%, B2O3 9.50, Bi2O3 6.44%, BaO 4.75%, and SrO 4.63%. Other components are the same as Example 1.

[0052] Comparative Example 14 A ceramic tile, which is different from Example 1 in that the average particle size of the surface glaze particles is 0.8 μm. Other aspects are the same as Example 1.

[0053] Comparative Example 15 A ceramic tile, which is different from the embodiment 1 in that the average particle size of the surface glaze particles is 10 μm. The other aspects are the same as the embodiment 1.

[0054] The ceramic tiles of Examples 1-17 and Comparative Examples 1-15 were tested, mainly to examine the fine texture of the glaze surface and the fineness of the glaze surface concave-convex gaps, wear resistance, hardness, and anti-fouling performance. Among them, the fineness of the glaze surface and the fineness of the concave-convex gaps are mainly determined by subjective observation and comparison methods; the wear resistance detection method is tested according to the provisions of the ceramic tile detection standard GB / T4100-2015.

[0055] Hardness testing method: glaze hardness, through Mohs hardness testing method. The ore for testing Mohs hardness is inlaid on a pen-shaped test tool on a metal rod, and the ore corners of the pen tip are used to scratch the object to be tested, and then the hardness of the object to be tested is judged based on whether scratches are left: if scratches are left, it means that the hardness of the object to be tested is lower than the hardness pen, and if scratches cannot be made, it means that the hardness of the object to be tested is higher than the hardness pen. The corresponding levels of the test materials used for Mohs hardness: talc: level 1, gypsum: level 2, calcite: level 3, fluorite: level 4, apatite: level 5, feldspar: level 6, quartz: level 7, topaz: level 8, corundum: level 9, diamond: level 10.

[0056] The testing method for anti-fouling performance is carried out in accordance with the provisions of the ceramic tile testing standard GB / T4100-2015.

[0057] The test results of the ceramic tiles of the embodiments and comparative examples are shown in Table 1, Table 2 and Table 3.

[0058] Table 1 Table 2 Table 3 It can be seen from Tables 1 to 3 that in Comparative Example 1, less barium-containing frit is used in the base glaze formula, and fewer crystals with a smooth texture are formed after firing, resulting in the glaze surface being not delicate and smooth enough. Figure 2As shown. In Comparative Example 2, there are more barium frits, which are too molten after firing and shrink greatly, resulting in uneven glaze surface 1. In Comparative Example 3, the fineness of the base glaze is too fine, and the shrinkage is too large during firing, resulting in an uneven glaze surface. In Comparative Example 4, the fineness of the base glaze is too large, and the liquid phase is not formed enough during the formula firing, resulting in a rough, uneven, and not delicate glaze surface. In Comparative Example 5, the content of bismuth trioxide in the digital protection glaze is too small, and the glass phase gaps are not filled enough, resulting in the glaze surface not being delicate enough. In Comparative Example 6, the content of bismuth trioxide in the digital protection glaze is too high, resulting in the glaze surface not being delicate and warm enough, and the concave and convex texture is not three-dimensional enough. In Comparative Example 7, the boron content in the digital protection glaze is relatively low, which affects the wear resistance and hardness of the product. In Comparative Example 8, the digital protection glaze contains a large amount of boron, which has a counter-effect, the glaze surface is dry, the wear resistance is low, and the concave and convex effect is not three-dimensional enough. In comparative example 9, the particle fineness of the digital protection glaze is coarse, and the gaps in the glaze surface are large after firing, resulting in a coarse glaze surface, which affects the maturity of the glaze surface after firing, resulting in low wear resistance and hardness. In comparative example 10, the amount of high borosilicate frit in the surface glaze is small, resulting in a small boron content, which directly affects the hardness and wear resistance of the glaze surface, and the concave-convex effect is poor. In comparative example 11, the content of high borosilicate frit in the surface glaze is too much, which causes too much oxide, forming a high temperature formula, and the glaze surface is not fine enough after firing, and the performance in all aspects is not good. In comparative example 12, the content of boron-bismuth frit in the surface glaze is too little, resulting in less boron and bismuth oxides, and the glass phase formed is mainly potassium-sodium glass phase, resulting in low wear resistance and hardness of the glaze surface, and the glaze surface is dry and rough due to less oxides. In comparative example 13, there are more boron-bismuth frits in the surface glaze, the formula temperature is low, mismatched, and the glaze surface is uneven after firing, and the wear resistance and hardness are low. In Comparative Example 14, the surface glaze has fine particles, which causes large shrinkage after firing, affecting the flatness of the glaze surface, and the concave-convex effect is not three-dimensional enough, and also affects various physical properties of the glaze surface. In Comparative Example 15, the surface particles are coarse, which directly causes the glaze surface to be rough after firing. At the same time, due to insufficient sintering degree, it causes insufficient wear resistance and hardness, and the concave-convex effect is not three-dimensional and fine enough.

[0059] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.

Claims

1. A ceramic tile with a gold velvet texture, characterized in that: From bottom to top, it includes base layer, base glaze layer, pattern layer, functional ink layer, digital protection glaze layer, and surface glaze layer; The base glaze layer is formed by a base glaze, and the base glaze comprises, by weight: 4-8 parts of air knife clay, 16-20 parts of calcined kaolin, 3-6 parts of calcined alumina, 10-15 parts of barium-containing frit, 15-23 parts of potassium feldspar, 12-20 parts of sodium feldspar, 12-18 parts of zircon white frit, 3-6 parts of burned talc, and 3-6 parts of wollastonite; The digital protection glaze layer is formed by a digital protection glaze, and the digital protection glaze comprises, by weight: 40-50 parts of an organic solvent and 50-60 parts of an inorganic glaze component; the inorganic glaze component comprises, by weight percentage: Al2O3 17.35%-20.17%, SiO2 55.68%-60.37%, K2O 1.38%-2.65%, Na2O 1.95%-3.01%, Bi2O3 2.13%-3.68%, B2O3 2.36%-4.65%, BaO 4.37%-6.58%, SrO 3.65%-5.68%; The surface glaze layer is formed by a surface glaze, and the surface glaze comprises, by weight: 4-8 parts of ball clay, 4-7 parts of corundum, 9-18 parts of high borosilicate frit, 18-25 parts of boron bismuth frit, 30-45 parts of monovalent oxide frit, 6-10 parts of barium carbonate, and 6-10 parts of strontium carbonate; The average particle size of the particles in the base glaze is 2 μm-8 μm; the average particle size of the particles in the digital protection glaze is 50 nm-100 nm; and the average particle size of the particles in the surface glaze is 1 μm-8 μm.

2. The ceramic tile according to claim 1, characterized in that: The chemical components of the base glaze include, by mass percentage, Al2O3 21.04%-24.56%, SiO2 50.24%-53.29%, K2O 1.34%-2.57%, Na2O 1.87%-2.65%, CaO0.80%-1.61%, MgO 1.21%-2.04%, BaO 6.31%-8.24%, and ZrO2 6.30%-8.64%.

3. The ceramic tile according to claim 1, characterized in that: The base glaze layer is formed by making the base glaze into a first slurry, and the preparation method of the first slurry is The method comprises the following steps: mixing the base glaze with 38-40 parts of water, 0.13-0.18 parts of sodium carboxymethyl cellulose and 0.25-0.35 parts of sodium tripolyphosphate, and performing ball milling to obtain the first slurry.

4. The ceramic tile according to claim 1, characterized in that: The chemical components of the high borosilicate frit include, by mass percentage, Al2O3 13.25%-15.35%, SiO2 68.39%-71.25%, B2O3 8.67%-11.25%, K2O 2.35%-4.67%, and Na2O 1.54%-2.68%.

5. The ceramic tile according to claim 1, characterized in that: The chemical components of the boron-bismuth frit include, by mass percentage, SiO2 56.31%-60.37%, Al2O3 13.64%-15.77%, B2O3 11.32%-14.65%, Bi2O3 8.62%-9.67%, K2O 1.35%-2.91%, and Na2O 1.11%-2.08%.

6. The ceramic tile according to claim 1, characterized in that: The chemical components of the monovalent oxide frit include, by mass percentage, K2O 4.56%-6.67%, Na2O 6.21%-9.34%, Li2O 4.63%-6.46%, SiO2 59.31%-63.34%, and Al2O3 16.69%-18.35%.

7. The ceramic tile according to claim 1, characterized in that: The chemical components of the surface glaze include, by mass percentage, Al2O3 15.38%-17.65%, SiO2 52.21%-54.61%, K2O 2.31%-3.45%, Na2O 1.35%-2.45%, Li2O 1.02%-1.89%, B2O3 6.65%-8.58%, Bi2O3 3.65%-5.94%, BaO 4.31%-5.98%, and SrO 4.64%-5.75%.

8. The ceramic tile according to claim 1, characterized in that: The surface glaze layer is formed by making the surface glaze into a second slurry, and the preparation method of the second slurry is The method comprises the following steps: mixing the surface glaze with 38-40 parts of water, 0.15-0.2 parts of sodium carboxymethyl cellulose and 0.3-0.4 parts of sodium tripolyphosphate, and performing ball milling to obtain the second slurry.

9. A method for preparing a ceramic tile according to any one of claims 1 to 8, characterized in that: The following steps are involved: Applying the base glaze on the base layer, then printing patterns and functional inks in sequence, and then applying the digital protective glaze and the surface glaze; The ceramic brick is obtained by firing.

10. The preparation method according to claim 9, characterized in that: The moisture content of the base layer is less than 0.3%, and the strength is 1.8 MPa-2.4 MPa; and / or the application amount of the base glaze is 380 g / m 2 -450 g / m 2 ; and / or, the application amount of the digital protective glaze is 70 g / m 2 -100 g / m 2 ; and / or, the application amount of the surface glaze is 180 g / m 2 -240 g / m 2 ; And / or, the firing conditions include: a firing time of 50 min-60 min and a firing temperature of 1180°C-1190°C.

Citation Information

Patent Citations

  • Self-releasing glaze ceramic and preparation method thereof

    CN111825428A

  • Wear-resistant antifouling protective glaze, matte ceramic tile and preparation method of matte ceramic tile

    CN114853346A

  • Digital low-light stone ceramic tile with skin texture as well as preparation method and application of digital low-light stone ceramic tile

    CN116693330A

  • Low-light stone ceramic tile with fine glaze and preparation method and application of low-light stone ceramic tile

    CN117447082A

  • Ceramic tile semifinished body having identification code, and spray-code identification-based ceramic tile printing method

    WO2022033464A1

Cited By

  • Golden velvet texture antifouling ceramic tile and preparation method thereof

    CN121021197A

  • A kind of anti-fouling ceramic tile with a velveteen texture and its preparation method

    CN121021197B